Antibiotic therapy for 6 or 12 weeks for prosthetic joint infection - Bernard, Louis; Arvieux, Cédric; Brunschweiler, Benoit; Touchais, Sophie; Ansart, Séverine; Bru, Jean-Pierre; Oziol, Eric; Boeri, Cyril; Gras, Guillaume; Druon, Jérôme; Rosset, Philippe; Senneville, Eric; et al. (New England Journal of Medicine, 2021)
BACKGROUND The management of prosthetic joint infection usually consists of a combination of surgery and antimicrobial therapy. The appropriate duration of antimicrobial therapy for this indication remains unclear. METHODS We performed an open-label, randomized, controlled, noninferiority trial to compare 6 weeks with 12 weeks of antibiotic therapy in patients with microbiologically confirmed prosthetic joint infection that had been managed with an appropriate surgical procedure. The primary outcome was persistent infection (defined as the persistence or recurrence of infection with the initial causative bacteria, with an antibiotic susceptibility pattern that was phenotypically indistinguishable from that at enrollment) within 2 years after the completion of antibiotic therapy. Noninferiority of 6 weeks of therapy to 12 weeks of therapy would be shown if the upper boundary of the 95% confidence interval for the absolute between-group difference (the value in the 6-week group minus the value in the 12-week group) in the percentage of patients with persistent infection within 2 years was not greater than 10 percentage points. RESULTS A total of 410 patients from 28 French centers were randomly assigned to receive antibiotic therapy for 6 weeks (205 patients) or for 12 weeks (205 patients). Six patients who withdrew consent were not included in the analysis. In the main analysis, 20 patients who died during follow-up were excluded, and missing outcomes for 6 patients who were lost to follow-up were considered to be persistent infection. Persistent infection occurred in 35 of 193 patients (18.1%) in the 6-week group and in 18 of 191 patients (9.4%) in the 12-week group (risk difference, 8.7 percentage points; 95% confidence interval, 1.8 to 15.6); thus, noninferiority was not shown. Noninferiority was also not shown in the per-protocol and sensitivity analyses. We found no evidence of between-group differences in the percentage of patients with treatment failure due to a new infection, probable treatment failure, or serious adverse events. CONCLUSIONS Among patients with microbiologically confirmed prosthetic joint infections that were managed with standard surgical procedures, antibiotic therapy for 6 weeks was not shown to be noninferior to antibiotic therapy for 12 weeks and resulted in a higher percentage of patients with unfavorable outcomes.

Preoperative and perioperative risk factors, and risk score development for prosthetic joint infection due to Staphylococcus aureus: a multinational matched case-control study - Espindola, Reinaldo; Vella, Venanzio; Benito, Natividad; Mur, Isabel; Tedeschi, Sara; Rossi, Nicolò; Hendriks, Johannes G.E.; Sorlí, Luisa; Murillo, Oscar; Scarborough, Mathew; Scarborough, Claire; Kluytmans, Jan; et al. (Clinical Microbiology and Infection, 2022)
Objectives We aim to identify the preoperative and perioperative risk factors associated with post-surgical Staphylococcus aureus prosthetic joint infections (PJI) and to develop and validate risk-scoring systems, to allow a better identification of high-risk patients for more efficient targeted interventions. Methods We performed a multicenter matched case-control study of patients who underwent a primary hip and knee arthroplasty from 2014 to 2016. Two multivariable models by logistic regression were performed, one for the preoperative and one for perioperative variables; predictive scores also were developed and validated in an external cohort. Results In total, 130 cases and 386 controls were included. The variables independently associated with S. aureus-PJI in the preoperative period were (adjusted OR; 95% CI): body mass index >30 kg/m2 (3.0; 1.9 to 4.8), resident in a long-term care facility (2.8; 1.05 to 7.5), fracture as reason for arthroplasty (2.7; 1.4 to 5.03), skin disorders (2.5; 0.9 to 7.04), previous surgery in the index joint (2.4; 1.3 to 4.4), male sex (1.9; 1.2 to 2.9) and American Society of Anesthesiologists index score 3 to 4 (1.8; 1.2 to 2.9). The area under the receiver operating characteristic curve was 0.73 (95% CI 0.68 to 0.78). In perioperative model, the risk factors were the previous ones plus surgical antibiotic prophylaxis administered out of the first 60 minutes before incision (5.9; 2.1 to 16.2), wound drainage for >72 hours after arthroplasty (4.5; 1.9 to 19.4) and use of metal bearing material versus ceramic (1.9; 1.1 to 3.3). The area under the receiver operating characteristic curve was 0.78 (95% CI 0.72 to 0.83). The predictive scores developed were validated in the external cohort. Discussion Predictive scores for S. aureus-PJI were developed and validated; this information would be useful for implementation of specific preventive measures.

Rates and Predictors of Treatment Failure in Staphylococcus aureus Prosthetic Joint Infections According to Different Management Strategies: A Multinational Cohort Study—The ARTHR-IS Study Group - Espíndola, Reinaldo; Vella, Venanzio; Benito, Natividad; Mur, Isabel; Tedeschi, Sara; Zamparini, Eleonora; Hendriks, Johannes G. E.; Sorlí, Luisa; Murillo, Oscar; Soldevila, Laura; Scarborough, Mathew; Scarborough, Claire; et al. (Infectious Diseases and Therapy, 2022)
Introduction Guidelines have improved the management of prosthetic joint infections (PJI). However, it is necessary to reassess the incidence and risk factors for treatment failure (TF) of Staphylococcus aureus PJI (SA-PJI) including functional loss, which has so far been neglected as an outcome. Methods A retrospective cohort study of SA-PJI was performed in 19 European hospitals between 2014 and 2016. The outcome variable was TF, including related mortality, clinical failure and functional loss both after the initial surgical procedure and after all procedures at 18 months. Predictors of TF were identified by logistic regression. Landmark analysis was used to avoid immortal time bias with rifampicin when debridement, antibiotics and implant retention (DAIR) was performed. Results One hundred twenty cases of SA-PJI were included. TF rates after the first and all surgical procedures performed were 32.8% and 24.2%, respectively. After all procedures, functional loss was 6.0% for DAIR and 17.2% for prosthesis removal. Variables independently associated with TF for the first procedure were Charlson ≥ 2, haemoglobin < 10 g/dL, bacteraemia, polymicrobial infection and additional debridement(s). For DAIR, TF was also associated with a body mass index (BMI) > 30 kg/m2 and delay of DAIR, while rifampicin use was protective. For all procedures, the variables associated with TF were haemoglobin < 10 g/dL, hip fracture and additional joint surgery not related to persistent infection. Conclusions TF remains common in SA-PJI. Functional loss accounted for a substantial proportion of treatment failures, particularly after prosthesis removal. Use of rifampicin after DAIR was associated with a protective effect. Among the risk factors identified, anaemia and obesity have not frequently been reported in previous studies.

Rates and Predictors of Treatment Failure in Staphylococcus aureus Prosthetic Joint Infections According to Different Management Strategies: A Multinational Cohort Study—The ARTHR-IS Study Group - Espíndola, Reinaldo; Vella, Venanzio; Benito, Natividad; Mur, Isabel; Tedeschi, Sara; Zamparini, Eleonora; Hendriks, Johannes G. E.; Sorlí, Luisa; Murillo, Oscar; Soldevila, Laura; Scarborough, Mathew; Scarborough, Claire; et al. (Infectious Diseases and Therapy, 2022)